PENGARUH TARI TOR-TOR BATAK TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL DESA KUMAIN KECAMATAN TANDUNKABUPATEN ROKAN HULU - Rosnani, Dahlia; Chairilsyah, Daviq; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The experimental study was aimed to determine the effect of Batak Tor-tor dance against Rough motor skills of children aged 5-6 years in kindergarten Aisyiyah Bustanul Athfal Village Kumain Tandun District of Rokan Hulu. The sample in this study were 15 children from 5-6 years old in kindergarten Aisyiyah Busthanul Athfal Village Kumain Tandun District of Rokan Hulu. The data collection techniques using observation sheet that contains the gross motor skills of children aged 5-6 years in kindergarten Aisyiyah Bustanul Athfal Village Kumain Tandun District of Rokan Hulu according to national education ministerial decree number 58 of 2009. Data were analyzed using t-test with using SPSS 23.0. The study hypothesis was a significant influence on the gross motor skills of children after the dance tor-tor Batak. It can be seen from the analysis of data obtained t = 15.370 and p = 0.000. Because p <0.05 it can be concluded that there are differences in gross motor skills of children significantly after the dance tor-tor Batak. So it means Ho rejected and Ha accepted which means there is a very significant difference between before and after the experiment with Batak Tor-tor dance.Key Word : Batak Tor-Tor Dance, Rough Motoric.